Gestation and breastfeeding in schistosomotic mice differentially alters the expression of histone deacetylases (HDACs) in adult offspring - Gabriela Calixto Ribeiro de Holanda; Fabrício Oliveira Souto; Maria da Conceição Silva; Virgínia Maria Barros de Lorena; Vlaudia Maria Assis Costa; Monica Camelo Pessôa de Azevedo Albuquerque; Valdênia Maria Oliveira de Souza; José Luiz de Lima Filho (Memorias do Instituto Oswaldo Cruz)
BACKGROUND Breastfeeding or gestation in schistosomotic mothers can cause long-term alterations in the immune response of offspring. OBJECTIVES Evaluate the expression of histone deacetylases (HDACs) (all classes), the production of cytokines by T and B lymphocytes and macrophages, and the frequency of CD4+CD25+FoxP3+-cells in adult offspring born and/or suckled by schistosomotic mothers. METHODS We harvested splenocytes from offspring born to (BIM), suckled by (SIM), or born to/suckled by (BSIM) schistosomotic mothers and animals from noninfected mothers (Control) at seven-weeks old and cultured them with/without Concanavalin A. HDAC expression was evaluated by real-time quantitative polymerase chain reaction (qPCR), and cytokines and membrane markers were evaluated by fluorescence-activated cell sorting (FACS). FINDINGS Compared to Control, BIM mice showed increased expression of HDAC9 and frequency of CD4+IL-10+-cells. The SIM group had increased expression of HDAC1, HDAC2, HDAC6, HDAC7, HDAC10, Sirt2, Sirt5, Sirt6, and Sirt7. The BSIM group only had increased HDAC10 expression. The SIM and BSIM groups exhibited decreased frequencies of CD4+IL-4+-cells and CD4+CD25+FoxP3+-cells, along with a higher frequency of CD14+IL-10+-cells and an increase in CD45R/B220+IL-10+-cells. The BSIM group also showed a high frequency of CD4+IL10+-cells. MAIN CONCLUSIONS Breastfeeding induced the expression of HDACs from various classes involved in reducing inflammatory responses. However, gestation enhanced the expression of a single HDAC and breastfeeding or gestation appears to favour multiple IL-10-dependent pathways, but not cells with a regulatory phenotype.